2017
DOI: 10.1093/jpepsy/jsw096
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Food Allergy Knowledge Test for Parents

Abstract: The FAKT was determined to have strong psychometrics and be appropriately reliable and valid, with clinical and research applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Two questions have multiple-choice answers listing symptoms (e.g., "Please indicate whether each of the following is a symptom of FA: mouth itching, hyperactivity, lip swelling…") for a possible score of 20 points. Prior research has shown the FAKT to demonstrate excellent internal consistency (Hahn et al, 2017). The internal consistency (Cronbach's alpha) in the current study was calculated to be .88 for the overall FAKT scale.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…Two questions have multiple-choice answers listing symptoms (e.g., "Please indicate whether each of the following is a symptom of FA: mouth itching, hyperactivity, lip swelling…") for a possible score of 20 points. Prior research has shown the FAKT to demonstrate excellent internal consistency (Hahn et al, 2017). The internal consistency (Cronbach's alpha) in the current study was calculated to be .88 for the overall FAKT scale.…”
Section: Methodsmentioning
confidence: 78%
“…functioning. (FAKT;Hahn et al, 2017). The FAKT is a 39-item measure intended to comprehensively assess FA illness knowledge for parents of children with FAs.…”
Section: Methodsmentioning
confidence: 99%
“…Caregivers were recruited from food allergy clinics in a large metropolitan area serving ethnically and financially diverse patients as part of a larger study aimed at developing and evaluating a measure of caregiver food allergy knowledge (the FAKT) (Hahn et al, 2011(Hahn et al, , 2017.…”
Section: Participantsmentioning
confidence: 99%
“…However, it is not yet clear to what extent food allergy knowledge and other caregiver characteristics specifically impact perceptions of safe versus unsafe food choices. The present study examined parents' general knowledge of food allergy (as measured by the Food Allergy Knowledge Test (FAKT; Hahn, Dahlquist, Hoehn, & Bollinger, 2017) in relation to parent's appraisals of whether or not certain foods were safe for their child to eat or should be avoided. Parents were given a list of foods and asked whether their child should avoid each food item.…”
mentioning
confidence: 99%
See 1 more Smart Citation